Integrating AI-Powered Mobile Immersive Technology for HSE Induction in an Oil and Gas Facility. A Conceptual Review - Naji , Gehad Mohammed Ahmed; Savita, KS; Kalid, Khairul Shafee (Journal of Ecohumanism, 2025)
The integration of AI-powered mobile immersive technology represents a transformative approach to enhancing Health, Safety, and Environment (HSE) induction procedures in oil and gas plants. This study investigates the significance and implications of adopting such technological innovations. By leveraging immersive mobile platforms and artificial intelligence (AI) algorithms, this novel methodology aims to revolutionize traditional HSE training practices. Employees engage in interactive modules and realistic simulations that replicate potential workplace hazards, safety protocols, and emergency scenarios, fostering an immersive learning environment. The research evaluates the advantages of this approach, including improved knowledge retention, heightened safety awareness, and enhanced decision-making skills among staff. It also addresses challenges associated with implementation, such as initial setup costs, data security concerns, and the need for continuous training and updates. The findings underscore how AI-powered mobile immersive technology can transform HSE induction processes in the oil and gas industry, leading to a safer and more efficient workplace. The study seeks to demonstrate the substantial impact of this innovative approach on traditional HSE training methodologies through the application of AI algorithms and immersive platforms.